Reality Counseling Based on The Board of Instructions for Student Hardiness - Ummah Karimah Syarifuddin; Wiwied Widiyanti; Oneng Nurul Bariyah; Sadari Sadari; Ahmad Irfan (Bulletin of Counseling and Psychotherapy, 2023)
Hardiness is needed by students when in boarding school. Phenomena experienced by students, such as feelings of not feeling at home, strict rules, busy activities, and adjusting to the conditions of the boarding school. The urgency of the research is to reveal the importance of boarding school-based Reality Counseling as a new innovation that researchers have made in counseling development, which combines boarding school culture with reality counseling developed by William Glasser. The purpose of this study is to explain the relationship between the educational objectives of the boarding school so that santri as humans have a relationship with God, namely as a human spiritual bridge and become a kaffah and tafaqquh fiddin person. The research data is supported by the results of pesantren-based reality counseling experiments conducted on Darul Rahman Ciganjur students, South Jakarta in developing students' spiritual hardiness with effective results in the commitment aspect. The research method in this study used research and development with quasi-experiments, the research subjects as participants were 11 students of class VIII MTs Ciganjur, South Jakarta. The procedure begins with preliminary studies, planning, implementation and results. To measure reality counseling using a questionnaire with statistical tests using the SPSS model. The results showed that reality counseling based on boarding school is effective for developing students' hardiness in the aspect of commitment, namely the average score (mean) of students' hardiness between before and after being given reality counseling services a significant increase in the average score of the commitment aspect, which is 1. It is concluded that this reality counseling can be used as a basis for developing strategies to develop students' hardiness in the aspect of commitment. The implication of the findings of this study is that boarding school can improve programs that can improve the hardiness aspects of students in control and challenge.